2020
DOI: 10.1111/1462-2920.14920
|View full text |Cite
|
Sign up to set email alerts
|

Sub‐seafloor biogeochemical processes and microbial life in the Baltic Sea

Abstract: The post-glacial Baltic Sea has experienced extreme changes that are archived today in the deep sediments. IODP Expedition 347 retrieved cores down to 100 m depth and studied the climate history and the deep biosphere. We here review the biogeochemical and microbiological highlights and integrate these with other studies from the Baltic seabed. Cell numbers, endospore abundance and organic matter mineralization rates are extremely high. A 100-fold drop in cell numbers with depth results from a small difference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 103 publications
4
36
0
Order By: Relevance
“…In the geochemically stable and low-energy conditions characteristic for the deep biosphere, it is suggested that microbes only occasionally have access to the “basal power requirement” for cell maintenance (e.g., biomass production and synthesis of biofilms, polymeric saccharides, etc.) or the costly process of duplication 8 , 9 . Inspecting the expression profile and metabolic context of actively transcribing microbes may reveal the dominant ecological strategies in the deep groundwater and uncover the dimensions of its available niches.…”
Section: Introductionmentioning
confidence: 99%
“…In the geochemically stable and low-energy conditions characteristic for the deep biosphere, it is suggested that microbes only occasionally have access to the “basal power requirement” for cell maintenance (e.g., biomass production and synthesis of biofilms, polymeric saccharides, etc.) or the costly process of duplication 8 , 9 . Inspecting the expression profile and metabolic context of actively transcribing microbes may reveal the dominant ecological strategies in the deep groundwater and uncover the dimensions of its available niches.…”
Section: Introductionmentioning
confidence: 99%
“…The TOC content was 3.9 ± 0.3%, and the acetate concentration was 5.9 ± 1.4 μM at 20–30 cm. Sediments from the bottom of the sulfate-reducing zone, located in the 20–30 cm horizon below sea floor ( Piker et al, 1998 ; Jørgensen et al, 2020 ), and with interesting target groups based on 16S rRNA amplicon sequencing, were selected as inocula and slurries were prepared without the addition of sulfate in order to induce highly reduced conditions ( Supplementary Table S3 ).…”
Section: Resultsmentioning
confidence: 99%
“…The microbial communities studied here originate from OM-rich sediments below oxygen-depleted waters in the Gotland basin in the Baltic Sea. Baltic Sea sediment microbial communities have been extensively studied across different environmental gradients ( Edlund et al, 2006 ; Thureborn et al, 2016 ; Marshall et al, 2017 ; Klier et al, 2018 ; Bird et al, 2019 ; Rasigraf et al, 2019 ; Zinke et al, 2019 ; Jørgensen et al, 2020 ), and the sedimentary OM content has been found to be one of the main defining factors of microbial community composition ( Edlund et al, 2006 ; Rasigraf et al, 2019 ; Zinke et al, 2019 ). This makes them an ideal model system to test the effects of OM type on the microbial community.…”
Section: Introductionmentioning
confidence: 99%
“…Methanogenesis and anaerobic methane oxidation (AMO) are highest in the SMTZ, where methanogenic Methanosarcina may form syntrophic associations with acetate oxidisers, e.g., Geobacter (Rotaru et al, 2018) and ANME-1 Archaea may conduct both methanogenesis and AMO (Beulig et al, 2019); in other sites, ANME-1 and/or ANME-2 Archaea have been implicated in AMO (Myllykangas et al, 2020b;Shubenkova et al, 2010;Treude et al, 2005). For a recent review on biogeochemical processes and microbial life in Baltic Sea sediments, including the deep biosphere, see Jørgensen et al (2020).…”
Section: Role Of Benthic Microbial Communitiesmentioning
confidence: 99%